A human Phase I/IIa malaria challenge trial of a polyprotein malaria vaccine. - Porter, D; Thompson, F; Berthoud, T; Hutchings, C; Andrews, L; Biswas, S; Poulton, I; Prieur, E; Correa, S; Rowland, R; Lang, T; Williams, J; et al. (2011)
We examined the safety, immunogenicity and efficacy of a prime-boost vaccination regime involving two poxvirus malaria subunit vaccines, FP9-PP and MVA-PP, expressing the same polyprotein consisting of six pre-erythrocytic antigens from Plasmodium falciparum. Following safety assessment of single doses, 15 volunteers received a heterologous prime-boost vaccination regime and underwent malaria sporozoite challenge. The vaccines were safe but interferon-γ ELISPOT responses were low compared to other poxvirus vectors, despite targeting multiple antigens. There was no vaccine efficacy as measured by delay in time to parasitaemia. A number of possible explanations are discussed, including the very large insert size of the polyprotein transgene.